PENERAPAN METODE POSE TO POSE PADA ANIMASI “LEGENDA BATANG BANGAU” - Afif, Muhammad Sayyid (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2023)
Animating is one part of the 3D animation production stage. Animating stage plays a big role in making an animated movie, because at this stage the movement of the character will be the determinant in delivering the story message in the animated movie. The problem that is often found in this animating process is that the movements made or produced still look stiff and make the story difficult to convey. Therefore, a way is needed so that the animation has a smooth movement and the message can be conveyed well. The pose to pose method is one way that can be used, so that the movement in an animated video or movie becomes smooth while still paying attention to existing animation principles. This research aims to apply the pose to pose method to the animated film "Legenda BatangBangau" and produce good animation quality.This research was conducted using a Luther-Sutopo metode. The author applies the pose to pose method to the animation, then writes down how the method is applied and what is found in the application of the method.By using the pose to pose method, animation creation becomes faster and more efficient.This research successfully applied the pose to pose method to the animation "Legenda Batang Bangau" and produced a good quality animation. This research is expected to help readers in producing good quality animation movements.